Racial prejudice and marginalisation of the Irish female migrants in the Irish Girl in America by Mary Anne Sadlier through the standpoint theory - M. Alashjaai, Nouf Fahad; Bahar, Ida Baizura; Haw Ching, Florence Toh; Mani, Manimanimangai (Human Resources Management Academic Research Society (HRMARS), 2024)
This paper focuses on The Irish Girl in America (1863) by the Irish author, Mary Anne Sadlier (1820-1903), who composed under the alias “J. Sadlier”. Her narratives are set against the cultural landscape of The Great Potato Famine (1845-1849) and depict the existence of Irish female transients of the 19th Century, which we contend is as yet understudied and overlooked in the educational curve on works of writing on the Irish female character. This is notwithstanding how authentic archives point out how the Irish female characters assisted with causing progressive acknowledgment of the Irish female outsiders’ presence. We hypothesise that the abstract portrayals of the Irish female migrants can be examined in The Irish Girl in America by Sadlier by zeroing how they accomplish advantaged stances as untouchables from inside the local host area. By utilising a hermeneutic, textual analysis, we centre around the author’s portrayals of the encounters of the slow arousing of the Irish female heroes by using “the stance hypothesis” by Sandra Harding (1986). Consequently, this study investigates the awareness for a self-definition through specific and aggregate degrees of accomplishing a “standpoint” experienced by the Irish female protagonists. Our findings uncover how the Irish female migrant characters can perform advantaged points of view and acknowledgment in their new local area.